2009
DOI: 10.4166/kjg.2009.54.5.269
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment Guidelines for Helicobacter pylori Infection in Korea

Abstract: Eleven years has passed since the guideline of the Korean College of Helicobacter and Upper Gastrointestinal Research group for H. pylori infection was produced in 1998. During this period the research for H. pylori has much progressed that H. pylori is now regarded as the major cause of gastric cancer. The seroprevalence of H. pylori in Korea was found to be decreased especially below the age of 40s and in the area of Seoul-Gyeonggi province, and annual reinfection rate of H. pylori has decreased up to 2.94%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
176
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 42 publications
3
176
0
2
Order By: Relevance
“…Korean guidelines, which were revised in 2013, by the Korean College of Helicobacter and Upper Gastrointestinal Research strongly recommend that H. pylori should be eradicated in patients with peptic ulcer disease, gastric MALT lymphoma, endoscopically treated early gastric cancer, and immune thrombocytopenic purpura [4]. Identification of optimal regimen of H. pylori eradication has been a challenge for gastroenterologists.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Korean guidelines, which were revised in 2013, by the Korean College of Helicobacter and Upper Gastrointestinal Research strongly recommend that H. pylori should be eradicated in patients with peptic ulcer disease, gastric MALT lymphoma, endoscopically treated early gastric cancer, and immune thrombocytopenic purpura [4]. Identification of optimal regimen of H. pylori eradication has been a challenge for gastroenterologists.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty years ago, one comparative study showed that proton pump inhibitor (PPI)-based triple therapy, that consisted of PPI, amoxicillin, and metronidazole, had superior efficacy for H. pylori eradication among various regimens based on PPI, bismuth, amoxicillin, and metronidazole [5]. In addition, conventional triple therapy, that consists of PPI, amoxicillin, and clarithromycin, has been widely used in Korea because of the high resistance rate of H. pylori against metronidazole [4,6,7]. This conventional triple therapy for 7-14 days is also a world-wide choice for H. pylori eradication [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eradication of H. pylori is the first option for the treatment of low-grade gastric MALT lymphoma. Furthermore, H. pylori eradication reduces the recurrence of peptic ulcer [4]. A recent Cochrane review reported that the risk of gastric cancer may be reduced through H. pylori eradication, particularly in Asia [5].…”
mentioning
confidence: 99%